Stories of misers in the legacy of writers (مجلة إحالات, 2026)
This research is a descriptive study of the phenomenon of Stinginess in the Arab legacy, and the view of some writers, like Al-Jahiz, Al-Baghdadi, Al-Abshihi, Al-Hanbali, Al-Tawhidi and Ibn Abd Rabbo, of the famous misers in that era and the previous eras as each of them spoke about the phenomenon of Stinginess in a distinctive way, so they mixed between seriousness and fun and they considered Stinginess as a social disease that must be treated, and these writers explained to us the impact of this phenomenon on society in its various aspects, through the stories they brought.